(untitled) (Fiep Bulletin - online, 2014)
The prevalence of childhood obesity can increase the incidence of early pubarche, which is a common form of sexual precocity occurring between six and seven years old and more commonly in females. Early adrenarche is the commonest etiology of early pubarche. The presence of these factors (obesity, early pubarche and early adrenarche) can increase the incidence of appearance of plurimetabolic syndrome, which can be diagnosed by both clinical and laboratorial criteria. The purpose of this study was to verify the influence of physical activity in children bearing plurimetabolic syndrome attending to a pediatric clinic in Maringá. Methods: This research was experimental, with a sample of 10 children aging from eight to nine years old, all female. The sample was chosen according to the following criteria: early pubarche through clinical diagnosis and bearers of plurimetabolic syndrome. All the patients were assessed at the beginning of the research for body mass index (BMI), blood pressure, laboratory exams of dyslipidemia (LDL, HDL and triglycerides) and blood glucose. The following values were found before the practice of physical activity (mean±standard deviation): BMI= 30±1.4kg/m2; LDL= 150±9.5mg/dL; HDL= 24.9±3.6mg/dL; Triglycerides= 135.1±10.6mg/dL; Glycemia= 142.3±6.2mg/dL; Systolic Pressure= 160±0.2mmHg; Diastolic Pressure= 109±0.1mmHg. The study lasted for six months with different intensities and amounts of training. Physical practice was carried out three times a week, for one hour each. At the sixth month, another check of the physiological parameters was made. The following results were obtained: BMI=22.2±0.8kg/m2; LDL= 106.1±3.8mg/dL; HDL= 47.5±3.7mg/dL; Triglycerides= 89.2±3.9mg/dL; Glycemia= 108.5±5.5mg/dL; Systolic Pressure= 111±0.1mmHg; Diastolic Pressure= 77.0±0.67mmHg. Taking into consideration the protocols of the III Brazilian Directives on dyslipidemia and of the Brazilian Society of Cardiology and Hypertension, it is observed that there was a statistically significant improvement on all the parameters evaluated.